Flight safety event management method as illustrated by a guided reactivity model - B. I. Bachkalo; S. D. Baynetov; S. G. Bolbat (Научный вестник МГТУ ГА, 2021)
The article provides a brief analysis of the problems of the existing flight safety management system in the state aviation of the Russian Federation, based on the lack of stable positive dynamics of accidents reduction. Brief conclusions from the analysis of the currently proposed scientific approaches for accidents reduction are given. The most significant practical results in the field of building a safety management system for a particular flight are considered. A new approach to the implementation of on-board flight safety management systems based on event management is proposed. The method of event-based safety management of a particular flight allows us to exclude the real time manifestation of known dangerous factors. To implement it, all processes related to known hazards are described in the form of events and assembled into complete groups of events. Control of the occurrence of the complete groups of events, their analysis and event management are carried out by event management models developed for each dangerous factor. When a certain number of events in one or several complete groups of events is reached, the aviation system protection algorithm, by preventing the occurrence of the remaining one or several events of the complete group, prevents erroneous actions of the crew, which prevents the occurrence of aviation incidents and accidents. As an example of the method implementation, the principle of forming an automated guided reactivity model of the event control contour for the dangerous factor "Violation of the Established Minimum Safe Parameters of the Aircraft Flight" in relation to an arbitrary maneuverable aircraft is considered in the article. The system, having registered the events that determine the group flight, is included into the analysis of dynamic elementary events determining the position of the wingman relating to the leading aircraft inside the event control contour in terms of range, angle of sight and altitude separation. When the parameters of one of the dynamic events approach the boundary of the event control contour, the system uses a recommendation or control action to set limits to the parameters not to go beyond the contour, which prevents the occurrence of erroneous actions of the crew.